1995
DOI: 10.1016/0275-5408(95)00098-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular motility, electrophysiological tests and visual fields in drug addicts

Abstract: The effects of drugs on intraocular motility, retina function and central pathways in a drug addicts population have been studied. The study group were made up of 15 drug addicts. Fifteen healthy subjects who had never used drugs acted as a control group. Refractive state, accommodation, tonometry, assessment of pupillary reflexes, campimetry, visual evoked cortical potential (VECP) and ERG were performed in all cases. All the subjects studied used heroine, 12 used cannabis and 12 used cocaine. Refraction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In addition, because electroretinography-measured cone voltages are known to be associated with (and perhaps predictive of ) visual field loss, [29][30][31] electroretinography testing was conducted on all patients in 5 sites where it was available on the same days as the visual field measures. Because cocaine abuse itself can produce electroretinography changes in a small fraction of users, 32 participants exhibiting such changes during screening were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, because electroretinography-measured cone voltages are known to be associated with (and perhaps predictive of ) visual field loss, [29][30][31] electroretinography testing was conducted on all patients in 5 sites where it was available on the same days as the visual field measures. Because cocaine abuse itself can produce electroretinography changes in a small fraction of users, 32 participants exhibiting such changes during screening were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…We found 15 articles evaluating the effects of various substances on ERG [6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Of these, nine studied the effects of cocaine, three studied cannabis, two studied alcohol, and one studied mixed drug use.…”
Section: Substance Usementioning
confidence: 99%
“…One case report described OCT imaging of subretinal blebs following vision loss in a strong hashish user [ 22 ]. González-Pérez et al found electroretinographic signal reduction in a cohort of Cannabis users, also suggesting photoreceptor damage [ 23 ]. Electroretinographic changes were also suggested by further studies in Cannabis users [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%